Analisa Dan Desain Sistem Informasi Penjualan Kendaraan Tunai dan Kredit Menggunakan Metode Agile - Rusmawan, Uus (INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS : Journal of Information System; Vol 9 No 1 (2024): INFORMATION SYSTEM FOR EDUCATORS AND PROFESSIONALS (Juni 2024), 2024)
The "Denira Arrahila" vehicle showroom is a shop that sells two-wheeled vehicles where the business is currently starting to develop and has plans to sell four-wheeled vehicles. At the start of opening a business, all transactions were recorded manually, then switched to using Excel. In line with this development, shop owners are experiencing several obstacles in the form of calculating installments if customers buy with a DP (Down Payment) with a changing amount, difficulty finding and displaying buyers who are in arrears on installments and calculating fines for late payment of these installments, there is no notification for consumers who installment payments will be due, calculation of vehicle sales price if done in cash or credit, sales transaction reports in cash or credit, installment payment reports and arrears reports cannot be displayed automatically with certain time criteria and other problems. Under these conditions, it is necessary to analyze and design a vehicle sales information system to reduce and overcome the obstacles above. Data and document collection methods were carried out by surveys and interviews. Application development is carried out using the Agile method because needs in the transaction process often change and require revisions or additions to certain features. Application testing is carried out using black box testing. Novelty from the research results in this application is in the form of calculating vehicle sales transactions in cash and credit which can be done automatically, there is a sales simulation with the down payment amount, vehicle price and length of installments, cash and credit sales reports, installment payment reports and arrears reports with various criteria. can be displayed periodically. This application really helps showroom owners in solving the problems they face.